2016
DOI: 10.18227/1982-8470ragro.v10i1.2462
|View full text |Cite
|
Sign up to set email alerts
|

Teor de óleo e proteína em grãos de soja em diferentes posições da planta

Abstract: Resumo: A posição da vagem na haste da planta constitui um dos vários fatores que influenciam a composição química dos grãos de soja. A interferência no conteúdo final de proteína e óleo pode resultar em erros de quantificação durante o processo de amostragem, importante em programas de melhoramento. Objetivou-se com este trabalho estudar o efeito da posição das vagens na planta no teor de óleo e proteína em cultivares de soja desenvolvidas para as condições de baixa latitude. Foram instalados dois experimento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
4
5
1
2
Order By: Relevance
“…The protein contents found in the cultivation in this research are similar or superior to those described in the literature for plants, such as soybean (40.4% DW in grain) and bran (46.7% DW) (Silva et al, 2006) with variations from 36.82 to 39.85% DW, depending on the region of the plant in which the grain was harvested (Sales et al, 2016). The values found in the present study are higher than those found in quinoa (14.1% DW), maize (9.4% DW) and rice (6.8% DW) (Nowak et al, 2016).…”
Section: Total Carbohydrates Water-soluble Proteins and Total Lipidssupporting
confidence: 82%
“…The protein contents found in the cultivation in this research are similar or superior to those described in the literature for plants, such as soybean (40.4% DW in grain) and bran (46.7% DW) (Silva et al, 2006) with variations from 36.82 to 39.85% DW, depending on the region of the plant in which the grain was harvested (Sales et al, 2016). The values found in the present study are higher than those found in quinoa (14.1% DW), maize (9.4% DW) and rice (6.8% DW) (Nowak et al, 2016).…”
Section: Total Carbohydrates Water-soluble Proteins and Total Lipidssupporting
confidence: 82%
“…For the same coverage to grow M5838 IPRO, it showed greater affinity for total oil in the grain (OG). Because it is a characteristic of soybeans to have high levels of oil in the grain (20%) and other chemical components, its composition is mainly influenced by climatic conditions and genetic conditions of cultivars (SALES et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The same happened for plant height and number of soybean plants. Sales et al (2016) state that the filling mechanisms of the grains with respect to the oil content are still incipient, but there is a negative correlation between the protein and oil content, i.e., the higher the protein content, the lower the oil content of the grain.…”
Section: Agronomic Analysis Of Soybeanmentioning
confidence: 99%